Innovation Eco Enzyme Based on Orange Peel Waste (Citrus Sinensis L.) and Citrus limon L. Burm in Making Environmentally Friendly Halal Detergent - Lisdiana, Linda; Windayani, Neneng; Kurniasih, Nunung; Farida, Ida (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2025)
The dual challenge of environmental degradation and the global demand for halal-certified products highlights the urgent need for sustainable and Sharia-compliant innovations in household cleaning agents. This study addresses the specific problem of formulating a detergent that is both environmentally friendly and halal by utilizing fermented orange peel waste (Citrus sinensis (L.)) and Citrus limon(L.) Burm. f to produce eco enzymes. Employing an experimental quantitative approach, the research investigates the production, formulation, and performance evaluation of eco enzyme-based detergents. Key tests included fermentation kinetics, pH analysis, organoleptic properties, and compliance with the Indonesian National Standard (SNI) for detergent quality specifically assessing cleaning efficacy, pH balance, foam stability, and user acceptability. The resulting eco enzyme exhibited a pH of 3 and a characteristic citrus aroma, while the formulated detergent demonstrated effective cleaning power and met all SNI criteria. This research not only offers a practical solution for reducing reliance on synthetic surfactants but also contributes to the growing body of halal green chemistry.